Thematic Analysis of Theses on Distance Education in Science Education - ZERMAN KEPCEOĞLU, Gülşah; PEKTAŞ, Murat (Bilgicagi Education Consulting and Publishing Industry Trade Limited Company, 2023)
The aim of the study is to analyze the postgraduate theses in the field of science education within the scope of distance education. The document analysis method was used in this study, adopting a qualitative approach. Within the scope of the research, 50 theses that are suitable for the purpose reached by YÖK National Thesis Center with the words "distance education" and "science" constitute the documents of the study. The theses were coded according to type, research approach, sample, data collection tools, and data analysis methods and then subjected to descriptive analysis by determining their frequencies and percentages. As a result of the research, it was concluded that the theses examined were mostly master's theses; nearly 50% of them used qualitative research methods. In addition, "teachers” were mainly preferred as the sample. Also, concerning the chosen research design, the data collection tools, and data analysis methods were appropriately selected.
Keywords: Distance education; science education; thematic analysis; Other Fields of Education (Other); Alan Eğitimleri (Diğer); 4. Education